2019
DOI: 10.5606/ehc.2019.66796
|View full text |Cite
|
Sign up to set email alerts
|

Icariin promotes early and late stages of fracture healing in rats

Abstract: Many plant-derived natural products have been used in traditional medicine for the treatment of various diseases. Herba Epimedii is a traditional herbal medicine that has been reported as an effective enhancer of bone healing, [1] and it has been stated that its extracts can reduce the occurrence of ÖZ Amaç: Bu çalışmada femur kırıklı sıçan modelinde lokal olarak uygulanan ikariinin kemik kırığı iyileşmesi üzerine etkileri değerlendirildi. Gereç ve yöntemler: Çalışmaya sekiz ana çalışma grubunda 64 erkek Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Thus, it is essential to explore an alternative drug for BMP-2. Recently, a traditional Chinese medicine Icariin, the main therapeutic component of a traditional medicine Herba Epimedii, is reported to be cost-efficient, osteoinductive, and nontoxic [78][79][80][81]. This makes it an attractive alternative for BMP-2 in bone tissue engineering; however, the half-life of Icariin is too short to maintain a therapeutic concentration in bone defects.…”
Section: Icariinmentioning
confidence: 99%
“…Thus, it is essential to explore an alternative drug for BMP-2. Recently, a traditional Chinese medicine Icariin, the main therapeutic component of a traditional medicine Herba Epimedii, is reported to be cost-efficient, osteoinductive, and nontoxic [78][79][80][81]. This makes it an attractive alternative for BMP-2 in bone tissue engineering; however, the half-life of Icariin is too short to maintain a therapeutic concentration in bone defects.…”
Section: Icariinmentioning
confidence: 99%
“…The effects of several substances on fracture healing have been examined in the literature. An animal model study by Gürbüz et al[ 4 ] showed that pentoxifylline accelerated fracture healing in the early period and delayed histological union in the late period in rats. As a result of radiological findings, pentoxifylline use was found to be ineffective on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Some agents like locally administered icariin facilitates bone healing via improving antioxidant responses within the fracture site. [ 4 ] When the inflammatory response begins to diminish, necrotic tissue and exudate are reabsorbed, and fibroblasts and chondrocytes emerge and begin to produce the new matrix and fracture callus. [ 5 ] Fracture hematoma acts as a skeleton made of fibrin to facilitate the activity of repair cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 - 7 ] Therefore, researchers have proposed various alternatives in order to accelerate fracture healing, and eliminate delayed union and non-union. [ 31 ] One of these alternatives is the use of stem cells on bony tissue. [ 9 ] Taguchi et al[ 10 ] have evaluated in vivo migration of bone marrow cells and their contribution to bone repair and shown that MSCs were definitely associated with bone healing.…”
Section: Discussionmentioning
confidence: 99%